The Utility of Animal Models for Studying the Metabo-Psychiatric Origins of Anorexia Nervosa - Zhang, Jie; Dulawa, Stephanie C. (Frontiers in Psychiatry, 2021)
Anorexia nervosa (AN) is a severe eating disorder that primarily affects young women and girls, and is characterized by abnormal restrictive feeding and a dangerously low body-mass index. AN has one of the highest mortality rates of any psychiatric disorder, and no approved pharmacological treatments exist. Current psychological and behavioral treatments are largely ineffective, and relapse is common. Relatively little basic research has examined biological mechanisms that underlie AN compared to other major neuropsychiatric disorders. A recent large-scale genome-wide association study (GWAS) revealed that the genetic architecture of AN has strong metabolic as well as psychiatric origins, suggesting that AN should be reconceptualized as a metabo-psychiatric disorder. Therefore, identifying the metabo-psychiatric mechanisms that contribute to AN may be essential for developing effective treatments. This review focuses on animal models for studying the metabo-psychiatric mechanisms that may contribute to AN, with a focus on the activity-based anorexia (ABA) paradigm. We also highlight recent work using modern circuit-dissecting neuroscience techniques to uncover metabolic mechanisms that regulate ABA, and encourage further work to ultimately identify novel treatment strategies for AN.